Calpeptin is neuroprotective against acrylamide-induced neuropathy in rats. (1st May 2018) - Su, Benyu; Guan, Qiangdong; Wang, Miaomiao; Liu, Ning; Wei, Xiaomin; Wang, Shue; Yang, Xiwei; Jiang, Wenchong; Xu, Mengmeng; Yu, Sufang
Highlights: Acrylamide (ACR) neuropathy model and calpeptin (CP) intervention model have been established in vitro and in vivo. CP has intervention effect on ACR-induced neurotoxicity. The mechanism of ACR-induced neuropathy is associated with the channel of calpain-MAP2 -MTs. Abstract: The aim of this study is to explore the potent neuroprotective effect of calpeptin (CP) on neuron damage induced by acrylamide (ACR) and its mechanism. Behavioural indicators such as hind limb splay, rota-rod performance, and gait analysis were assessed weekly to evaluate neurobehavioural changes after ACR and/or CP administration. The histopathological alterations and the changes of μ-calpain, m-calpain, microtubule-associated protein 2 (MAP2), and α-tubulin and β-tubulin protein levels in spinal cord were determined. Results showed that after administration of 30 mg/kg ACR, decreased body weight, attenuated neurobehavioural function, injury of motor neuron, increased protein levels of m-calpain and β-tubulin, suppressed MAP2 protein level, and no significant changes of μ-calpain and α-tubulin protein levels were observed compared with the control group rats. After administration of 200 μg/kg CP, partially restored body weight and neurobehavioural function, improvement of motor neuron injury, decreased protein levels of m- calpain and β-tubulin, and reversed effects of MAP2 protein level were observed compared with the ACR group rats. Our results suggested that CP alleviates neuropathy induced by ACR in rats. The calpain's overactivation causes the degrading of MAP2 and eventually leads to the destruction of microtubules (MTs), which may be one of the mechanisms of cytoskeletal damage induced by ACR.